Whole genome and transcriptome profiling in advanced pancreatic cancer patients on the COMPASS trial - Jennifer J. Knox; Gun Ho Jang; Robert C. Grant; Amy Zhang; Lucy Ma; Elena Elimova; Raymond Jang; Malcolm Moore; James Biagi; Mustapha Tehfe; Ravi Ramjeesingh; Erica S. Tsang; et al. (Nature Communications)
Abstract Integrated whole genome and transcriptome sequencing can unveil distinct molecular subgroups in pancreatic cancer (PDAC). The COMPASS trial (NCT02750657) enrolled 268 patients with advanced PDAC; patients were given either modified (m) FOLFIRINOX or Gemcitabine-nab-paclitaxel (GnP) as per physicians choice. Median follow-up is 52 months and median overall survival in those receiving mFOLFIRINOX is 10.6 months and 8.4 months for GnP. KRAS specific mutants and allelic states alone are not prognostic; however basal-like PDAC are more likely to harbour major imbalances in mutant KRAS (KRASmaj). In the presence of KRASmaj, pre-existing type II DM is more common. Distinct prognostic cohorts include homologous-recombination deficient PDAC, predictive of mFOLFIRINOX response. Basal-like PDAC and patients exhibiting evidence of systemic inflammation as annotated using the Gustave Roussy Immune Score are unique poor prognostic cohorts. The latter associates with low CD8 T cell infiltration while basal-like PDAC documents an inflamed tumour microenvironment.